2018
DOI: 10.1186/s12866-018-1205-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing and identification of Bacillus endophyticus and B. anthracis isolated from anthrax outbreaks in South Africa

Abstract: BackgroundBacillus endophyticus is a soil plant-endophytic bacterium, while B. anthracis is the causative agent of anthrax. The virulence factors of B. anthracis are the plasmid encoded tripartite toxins (pXO1) and poly-γ-glutamic acid (PGA) capsule (pXO2). B. endophyticus isolated alongside B. anthracis from animals that died of anthrax in Northern Cape Province (NCP), South Africa, harbored polyglutamate genes. The study compared the characteristics of B. anthracis and B. endophyticus with other Bacillus spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The identification of species closely related to B. anthracis on diagnostic blood smears can complicate anthrax diagnosis as these species may share similar genetic markers with B. anthracis , leading to false positive results from molecular diagnostics. In addition, other genera, such as Peribacillus and Priestia (Loong et al, 2017, Lekota et al, 2018), can also complicate anthrax diagnosis. These species may not share as many genetic markers with B. anthracis as the B. cereus group, but still have some similarities that could lead to false positive results as seen in this study when performing qPCR diagnostics using only lef , Ba-1, or pagA (BAPA) markers (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of species closely related to B. anthracis on diagnostic blood smears can complicate anthrax diagnosis as these species may share similar genetic markers with B. anthracis , leading to false positive results from molecular diagnostics. In addition, other genera, such as Peribacillus and Priestia (Loong et al, 2017, Lekota et al, 2018), can also complicate anthrax diagnosis. These species may not share as many genetic markers with B. anthracis as the B. cereus group, but still have some similarities that could lead to false positive results as seen in this study when performing qPCR diagnostics using only lef , Ba-1, or pagA (BAPA) markers (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Lekota et al (2018) demonstrated that the capsular region or polyglutamate regions ( capABC ) are the ones that complicate anthrax diagnosis. Lekota et al (2018) reported that capC is not specific to B. anthracis . Thus, combining capsule markers such as the capB in this study with other markers increased the specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found a species of Bacillus ( B. endophyticus ) that significantly promotes growth of Coccidioides . This species of Bacillus has been co-cultured with other pathogens and has been implicated in providing virulence factors via plasmid exchange [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, colonial characteristics and the Gram staining reaction of DPM17 were in general agreement with those reported for Bacillus sp. [42].…”
Section: Discussionmentioning
confidence: 99%